PUBLIC RELATIONS CAMPAIGN MANAGEMENT IN PREVENTING COVID-19 THROUGH INSTAGRAM SOCIAL MEDIA AT TELKOM UNIVERSITY OF BANDUNG - Deden Ramdan (Jurnal Scientia, 2023)
This research is titled "Public Relations Campaign Management in Covid-19 Prevention through Instagram Social Media at Telkom University Bandung." The research focuses on the public relations campaign management of Telkom University Bandung regarding the prevention of Covid-19 spread through Instagram social media. The first informant is the authorized personnel responsible for managing Telkom University Bandung's social media and conducting Covid-19 health communication campaigns. The second informant consists of the academic community of Telkom University Bandung, including professors, educators, students, and the general public who receive health communication campaign information through Telkom University Bandung's social media. The method used in this research is qualitative research with the campaign theory taken from Venus and the communication theory taken from Laswell. The results obtained from this research broadly cover the Health Communication Campaign in dealing with the Covid-19 pandemic conducted by Telkom University Bandung. The researcher analyzed that the campaign has been quite successful.